Setup Time Reduction in an Automotive Battery Assembly Line - Deros, B.M.; Mohamad, D.; Idris, M.H.M.; Rahman, M.N.A.; Ghani, J.A.; Ismail, A.R. (Applied Science and Engineering Progress, 2013)
One of the most critical challenges faced by many manufacturing industries is to produce high quality products using cost-efficient methods and tools in the shortest possible time and at the lowest operating costs. Many past researches had shown that in order to reduce setup time and manufacturing costs it need for fast setups and changeovers. Single Minute Exchange of Die (SMED) is one of the Lean Manufacturing System (LMS) tools used to measure setup and changeover efficiency. Setup time reduction is an important key parameter for improving manufacturing flexibility and reducing manufacturing costs. The three main objectives of this study are: first, to reduce machine setup time by 35% during a mould changeover; second, to identify the root causes of the bottlenecks operations; third, to propose and implement possible solutions to the bottleneck problems. SMED methods were applied at two major bottlenecks during setup operations, they are cast on strap and heat seal. Results and findings on the data analysis of the two bottlenecks before and after implementation of SMED are examined and analyzed. The setup operations performance is measured based on data analysis result with respect to machine setup time reduction. The result of this study shows significant reduction of cast on strap setup time to 54% and heat seal setup time to 47%. In other words, this study has achieved more than 35% of setup time reduction.